Characteristics of ASTM A36 steel plate corrosion rate due to bending treatment with angle, corrosion media, and corrosion time variations - Muhamad Zainal Arifin; Djoko Kustono; Widiyanti Widiyanti (Faculty of Engineering, Universitas Negeri Yogyakarta, 2020)
Bending can cause stress to the workpiece, where the stress can cause a fine crack in the metal which can lead to corrosion. Corrosion that occurs can result in a decline in the quality of metals, especially in mechanical properties. This study aims to determine the characteristics of the corrosion rate of each bending angle. This study uses low carbon steel with ASTM A36 type plates, this type of steel is often used in ship production. This research is an experimental study using descriptive statistical methods, and 3x3 factorial Anava for testing hypotheses. From this research, the results obtained in the form of corrosion rate values, where the characteristics of the corrosion rate of steel plates with the lowest corrosion resistance are at 60o bending treatment, seawater media, and 48 hours with a corrosion rate of 2.005 mmpy. Corrosion rate characteristics with the best resistance are in the bending treatment of 120o, PDAM water media, and 24 hour time with a corrosion rate of 0.695 mmpy. Hypothesis test results state that there is a significant effect of variations in bending angle, corrosion media, and corrosion time on the value of the corrosion rate.